Effect of Dietary Inclusion of Protected Sodium Butyrate on the Digestibility and Intestinal Histomorphometry of Commercial Laying Hens - MF Pires; NSM Leandro; HF Oliveira; DV Jacob; FB Carvalho; JH Stringhini; DP Carvalho; CL Andrade (Brazilian Journal of Poultry Science, 2021)
ABSTRACT The objective of this study was to evaluate the effects of dietary inclusion of protected sodium butyrate (PSB) on the intestinal development and feed nutrient metabolizability of commercial laying hens. The birds started to receive the treatment rations at 58 weeks of age. At 76 weeks of age the laying hens were distributed in a randomized block design to four treatments (0, 105, 210 and 300 g t-1/PSB), six replicates, and two birds/replicate. The nitrogen balance (NB), ether extract balance (EEB), dry matter metabolizability coefficient, nitrogen, ether extract, ash, apparent metabolizable energy (AME), and AME corrected by nitrogen (AMEn) were evaluated. For assessment of intestinal development, we evaluated the duodenum, jejunum, ileum, cecum, and colorectal lengths, the relative intestine weight and villus height, crypt depth, and villus:crypt ratio of the duodenum, jejunum, and ileum. A decreasing linear effect was observed in the duodenum length, while an increasing linear effect was observed in the height of the duodenum and jejunum villi. A quadratic effect was found in the jejunum crypt depth. A linear increasing effect was found on the villus:crypt ratio of the duodenum and jejunum, and a quadratic effect was observed in the ileum. Quadratic and increasing linear effects were observed in the NB and EEB, respectively. Additionally, increasing linear effects were observed in the AME and AMEn. The dietary addition of 300 g t-1 of PSB improved intestinal development and energy metabolizability of the diet.